Comprehensive Transcriptomics and Biochemical Analysis Provide New Insights into the Light Intensity Regulation Growth and Medicinal Quality of Dendrobium nobile - Ting Li; Haolin Liu; Yijun Fan; Hui Wang; Linlong Xu; Siyu He; Jie Ma; Junlan Wu; Chunhong Mou; Meng Zhao; Li Chen; Xuyang Liu; et al. (Journal of Plant Growth Regulation, 2026)

An ultrasound-driven bioengine for apoptosis inhibition and immune homeostasis regulation in intervertebral disc degeneration - Dengbo Yao; Linlong Li; Yu Tang; Juntao Yao; Hang Liu; Jie Weng; Yu Wang; Qingquan Kong; Huan Tan (Chemical Engineering Journal, 2026)

Enhanced puncture event detection for teleoperated needle insertion robotic system - Hongbing Li; Yubin Lan; Yuling Li; Linlong Li; Rui Wang (Medical & Biological Engineering & Computing, 2026)

Experimental study on pitch motion mitigation of a 15 MW spar wind turbine using passive gyro stabilizers - Junlei Wang; Haoran Li; Jisheng Zhang; Dawei Guan; Linlong Tong; Hao Chen; Xiaoqiang Kou (Ocean Engineering, 2026)

Reducing local scour around monopiles using arc-shaped sacrificial piles under unidirectional flow - Hao Chen; Jisheng Zhang; Hao Hu; Linlong Tong; Yiming Ji; Haoran Li; Yanhong Wang (Ocean Engineering, 2026)

Ultrasensitive detection of prostate-specific antigen via nanogap metasurface sensor - Xiaoxuan Li; Linlong Tang; Xiaojian Zhang; Changhao Song; Xiaohong Zhang; Jinpeng Nong; Antonio Frisoli; Yu Li; Wei Wei (Chemical Engineering Journal, 2026)

Experimental study of the seabed responses induced by a floating column with a heave plate - Yiming Ji; Linlong Tong; Jisheng Zhang; Haoran Li; Hao Chen; Yakun Guo; Shoupeng Xie (Coastal Engineering, 2026)

Bimetallic synergism-driven Au0.75Pt0.25 nanoparticles-modified SnO2 heterojunction nanostructures for ultrasensitive detection of carbonate-based electrolyte leakage gases towards battery safety applications - PeiJiang Cao; LinLong Qu; YuWei Li; Fang Jia; YuXiang Zeng; DeLiang Zhu; ChunFeng Wang; Shun Han; Ming Fang; XinKe Liu; WenJun Liu; Sachin T. Navale (Chemical Engineering Journal, 2026)

Physiological and Secondary Metabolism of Dendrobium nobile Lindl in Response to High Temperature Stress - Linlong Xu; Yijun Fan; Xueyan Tan; Jie Ma; Ting Li; Siyu He; Hui Wang; Liangjie Zhu; Le Zeng; Aoxue Luo (Journal of Plant Growth Regulation, 2026)

Experimental study of bimodal spectral wave-induced dynamic responses in a silty seabed - Linlong Tong; Zhen Huang; Jisheng Zhang; Ning Chen; Dong-Sheng Jeng; Shulin Zhao; Xueyan Li (Coastal Engineering, 2026)

Rate-dependent uplift behavior and soil failure mechanisms of suction anchors in loose sand: a transparent soil PIV study - Tao Zhou; Linlong Mu; Yimin Lu; Meihe Chen; Maosong Huang; Yuxuan Li (Ocean Engineering, 2025)

Global Fixed-Time Target Enclosing Tracking Control for an Unmanned Surface Vehicle Under Unknown Velocity States and Actuator Saturation - Xinjie Han; Guanglu Ma; Yunsheng Fan; Dongdong Mu; Feng Sun; Linlong Shi; Hongbiao Li (Journal of Marine Science and Engineering, 2025)
This paper presents a global fixed-time control framework to address the target circumnavigation tracking problem of underactuated unmanned surface vehicles (USV) under unknown velocity states, lumped uncertainties, and actuator saturation. At the core of this approach is a novel fixed-time target-enclosing line-of-sight (FTTELOS) guidance law, designed to generate the desired heading angle and surge velocity. To estimate unknown velocities, external disturbances, and unmeasured system states, a set of fixed-time observers is constructed, consisting of a velocity observer, a disturbance observer, and a high-dimensional extended state observer (HFTESO). Moreover, to enhance robustness and effectively tackle actuator saturation, the control scheme incorporates a fixed-time sliding mode controller, a dynamic auxiliary system, and a fixed-threshold event-triggered mechanism. Simulation results using SimuNPS demonstrate that the proposed method enables rapid and smooth target circumnavigation, with all system errors converging to an arbitrarily small neighborhood of the origin within a fixed time. Theoretical analysis and simulation studies confirm the effectiveness and robustness of both the FTTELOS guidance law and the integrated control strategy. Quantitatively, compared with the traditional target-enclosing line-of-sight (TELOS) method, the proposed FTTELOS reduces the convergence time of the distance error δe from 13.64 s to 10.22 s and the angular error ϕe from 10.46 s to 7.52 s, demonstrating a significant improvement in convergence speed and overall control performance.

Domain-decomposed physics-informed neural network for one-dimensional soil consolidation under multi-step surcharge loading - Hao Zhang; Bokai Song; Linlong Zuo; Lin Li (Transportation Geotechnics, 2025)

Nonlinear long waves over a rigid porous seabed - Linlong Tong; Chao Xu; Jisheng Zhang; Zhiyuan Yang; Haoran Li; Xianju Xie (Ocean Engineering, 2025)

Hofmeister effect-assisted chain bundling and limited coalescence in Pickering emulsion to construct tough and conductive scaffolds for bone regeneration - Huan Tan; Linlong Li; Xue Bai; Yu Deng; Shichen Hu; Yuanyuan Zhou; Shirun Chu; Zili Guo; Jiahao Zhang; Hua Li; Jie Weng (Chemical Engineering Journal, 2025)

Long-term effects of environmental changes on taxonomic, functional, and phylogenetic alpha and beta diversity of fish communities in the Minjiang Estuary - Pengzhan Zhang; Yuru Li; Xin Peng; Linlong Wang; Yefu Kong; Hao Tian; Bin Kang (Environmental Biology of Fishes, 2025)

Statistical characteristics of turbulence in combined wave-current boundary layer flows - Xuan Zhang; Jinhai Zheng; Chi Zhang; Jisheng Zhang; Yakun Guo; Linlong Tong; Rupeng Wang; Haoran Li (Ocean Engineering, 2025)

Modeling the reachable set of ships in the presence of realistic wave disturbances - Dongdong Mu; Xiaomeng He; Mingyang Yin; Hongbiao Li; Linlong Shi; Yunsheng Fan; Xiaojie Sun (Ocean Engineering, 2025)

Light intensity is a crucial factor that regulates growth, physiological traits, antioxidant defense, and metabolite acquisition in Dendrobium denneanum - Hui Wang; Siyu He; Yijun Fan; Ting Li; Linlong Xu; Jie Ma; Junlan Wu; Haolin Liu; XuYang Liu; ChunHong Mou; Meng Zhao; Li Chen; et al. (Physiology and Molecular Biology of Plants, 2025)

Enhancement of PPCPs photodegradation in stormwater runoff by sulfur vacancy-induced ZnS1-x/ZnO on permeable concrete - Muzi Li; Xiaojuan Bai; Linlong Guo; Zhaoying Liu; Meipeng Jian; Chaohong Tan; Hongxiang Chai; Haiyan Li (Journal of Water Process Engineering, 2025)

Prioritizing the multifaceted community and species uniqueness for the conservation of lacustrine fishes in the largest subtropical floodplain, China - Yang Liu; Yang Yan; Li Lin; Linlong Wang; Yanping Zhang; Bin Kang (Journal of Environmental Management, 2024)

Novel high-purity struvite crystallization method for phosphate recovery from simulated swine wastewater using activated talcum - Linlong Li; Han Li; Haiming Huang; Xiaotong Kuang; Leyao Tao; Caiying Zhu (Journal of Cleaner Production, 2024)

Simultaneous manipulation of constituent and structure toward MOFs-derived hollow Co3O4/Co/NC@MXene microspheres via pyrolysis strategy for high-performance microwave absorption - Linlong Xing; Haoran Cheng; Yang Li; Qiang Chen; Xianhu Liu (Chemical Engineering Journal, 2024)

Ca–Mg modified attapulgite for phosphate removal and its potential as phosphate-based fertilizer - Xiaotong Kuang; Jing Li; Zhu Ouyang; Haiming Huang; Jingjing Chen; Xingtong Chen; Linlong Li (Journal of Environmental Management, 2024)

Applicability and sensitivity analysis of vector cellular automata model for land cover change - Yao Yao; Ying Jiang; Zhenhui Sun; Linlong Li; Dongsheng Chen; Kailu Xiong; Anning Dong; Tao Cheng; Haoyan Zhang; Xun Liang; Qingfeng Guan (Computers, Environment and Urban Systems, 2024)

Transcriptomics combined with physiological analysis provided new insights into the Zn enrichment capacity and tolerance mechanism of Dendrobium denneanum Kerr - Yuanyuan Liu; Erya Xu; Yijun Fan; Linlong Xu; Jie Ma; Xuebing Li; Hui Wang; Siyu He; Ting Li; Yujiao Qin; Jingtao Xiao; Aoxue Luo (Plant Science, 2024)

The Impact of Pre-Existing Faults on Fault Geometry during Multiphase Rifts: The Jiyang Depression, Eastern China - Di Wang; Linlong Yang; Wei Li; Xidong Wang (Journal of Marine Science and Engineering, 2023)
The combination of multi-phase extension and pre-existing fault reactivation results in a complex fault pattern within hydrocarbon-bearing basins, affecting hydrocarbon exploration at different stages. We used high-resolution 3D seismic data and well data to reveal the impact of multi-phase extension and pre-existing fault reactivation on Cenozoic fault pattern changes over time in the Jiyang Depression of eastern China. The results show that during the Paleocene, a portion of NW-striking pre-existing faults reactivated under NS extension and controlled the basin structure (type 1). Other parts of the NW-striking pre-existing faults stopped activity and served as weak surfaces, and a series of NNE-striking faults were distributed in an en-echelon pattern along the NW direction at shallow depths (type 2). In areas unaffected by pre-existing faults, NE-striking faults formed perpendicular to regional stresses. During the Eocene, the regional stresses shifted clockwise to near-NS extension, and many EW-striking faults developed within the basin. The NE-striking faults and the EW-striking faults were hard-linked, forming the ENE-striking curved faults that controlled the structure in the basin (type 3). The NNE-striking faults were distinctly strike-slip at this time, with the ENE-striking faults forming a horsetail pattern at their tails. Many ENE-striking faults perpendicular to the extension direction were formed in areas where the basement was more stable and pre-existing faults were not developed (type 4). There were also developing NS-striking faults that were small in scale and appeared in positions overlapping different main faults (type 5). Additionally, different fault patterns can guide different phases of hydrocarbon exploration. Type 1, type 2, and type 3 faults are particularly suitable for early-stage exploration. In contrast, type 4 and type 5 faults are more appropriate for mature exploration areas, where they may reveal smaller hydrocarbon reservoirs.

Fish growth evaluation and fishery dynamic assessment of Harpadon nehereus providing insights for its population expansion in the Northern East China Sea - Linlong Wang; Jintao Li; Bin Kang (Hydrobiologia, 2022)

Root-associated microbiota drive phytoremediation strategies to lead of Sonchus Asper (L.) Hill as revealed by intercropping-induced modifications of the rhizosphere microbiome - Xinyue Mei; Ying Wang; Zuran Li; Marie Larousse; Arthur Pere; Martine da Rocha; Fangdong Zhan; Yongmei He; Linlong Pu; Franck Panabières; Yanqun Zu (Environmental Science and Pollution Research, 2022)
Intercropping or assistant endophytes promote phytoremediation capacities of hyperaccumulators and enhance their tolerance to heavy metal (HM) stress. Findings from a previous study showed that intercropping the hyperaccumulator Sonchus asper (L.) Hill grown in HM-contaminated soils with maize improved the remediating properties and indicated an excluder-to-hyperaccumulator switched mode of action towards lead. In the current study, RNA-Seq analysis was conducted on Sonchus roots grown under intercropping or monoculture systems to explore the molecular events underlying this shift in lead sequestering strategy. The findings showed that intercropping only slightly affects S. asper transcriptome but significantly affects expression of root-associated microbial genomes. Further, intercropping triggers significant reshaping of endophytic communities associated with a ‘root-to-shoot’ transition of lead sequestration and improved phytoremediation capacities of S. asper . These findings indicate that accumulator activities of a weed are partially attributed to the root-associated microbiota, and a complex network of plant–microbe-plant interactions shapes the phytoremediation potential of S. asper . Analysis showed that intercropping may significantly change the structure of root-associated communities resulting in novel remediation properties, thus providing a basis for improving phytoremediation practices to restore contaminated soils.

A framework of analytical methods for horizontal behaviours of monopiles under V-H-M loads in sand - Linlong Mu; Wei Chen; Yiming Zhang; Xiaoxiang Chen; Wan Li (Marine Georesources & Geotechnology, 2022)

Fishery Status and Rebuilding of Major Economic Fishes in the Largest Freshwater Lake in China Based on Limited Data - Yang Liu; Huiyun Fu; Linlong Wang; Li Lin; Gang He; Peifeng Fu; Changlai Wang; Yanping Zhang; Bin Kang (Fishes, 2022)
Poyang Lake, the largest freshwater lake in China, possesses abundant fishery resources, but its fish stock status is still unclear. In this work, the stock status of and fishing efforts of nine major economic fishes in the Poyang Lake were estimated from 2000 to 2019 with a catch-based maximum sustainable yield (CMSY) model based on catch and resilience data. It was further predicted whether the biomass of those fishes could be restored to support maximum sustainable yield (Bmsy) under the policy of “Ten years fishing moratorium in the Yangtze River”. The results showed that goldfish Carassius auratus, grass carp Ctenopharyngodon idella, and black carp Mylopharyngodon piceus suffered from higher fishing efforts and low biomass in the past 20 years; bighead carp Hypophthalmichthys nobilis, yellow catfish Tachysurus fulvidraco, and common carp Cyprinus carpio responded differently to their fishing efforts; silver carp Hypophthalmichthys molitrix, Amur catfish Silurus asotus, and mandarin fish Siniperca chuatsi were underexploited. Six species were overfished in 2019, and their biomass would be expected to recover for sustainable exploitation during the fishing moratorium, except for M. piceus. This study provided a case study of feasible freshwater fishery evaluation in limnetic ecosystems.

Fishery Dynamics, Status, and Rebuilding Based on Catch-Only Data in Coastal Waters of China - Linlong Wang; Li Lin; Yang Liu; Lu Zhai; Shen Ye (Frontiers in Marine Science, 2022)
China has become the largest contributor to marine fisheries in the world with its fishing fleets explosively increasing their fishing effort and resulting catch, but its fishery composition and sustainability have deteriorated. Limited information on fishery exploitation status encumbers effective resource management. In this study, a data-poor Monte Carlo method, the Catch-Maximum Sustainable Yield (CMSY) method, was used to estimate the historical exploited dynamics and current stock status of ten Chinese economic marine fish stocks, including Trichiurus lepturus , Larimichthys crocea , Larimichthys polyactis , Thamnaconus modestus , Scomberomorus niphonius , Ilisha elongate , Decapterus maruadsi , Scomber japonicus , Engraulis japonicus , and Clupea pallasii , which accounted for about 50% of total fish catches in the coastal waters of China and covered five functional groups (i.e., large, medium benthopelagic, large, medium, and small pelagic). Species L. crocea and L. polyactis had been subjected to overfishing since the 1950s. The others showed a decreasing trend in biomass along with the explosively increasing fishing efforts since the 1990s. Benthopelagic fish experienced overfishing pressure about a decade earlier than pelagic species. All the fish stocks investigated in this study were depleted (current biomass lower than the biomass capable of producing maximum sustainable yields, i.e., B < B msy ) in 2019, and most species were still facing high-fishing pressure (current fishing mortality higher than the mortality capable of producing maximum sustainable yields, i.e., F > F msy ). Also, a Schaefer model was used to assess stocks rebuilding status until 2030 under four exploitation scenarios, i.e., fishing mortality equals 0.5, 0.6, 0.8, or 0.95 times F msy . Most species stocks will likely recover to the B msy , which indicates that reduction of fishing pressure is probably the most effective way for fishery recovery.

Redistribution of the lizardfish Harpadon nehereus in coastal waters of China due to climate change - Linlong Wang; Zhixin Zhang; Longshan Lin; Xin Peng; Li Lin; Bin Kang (Hydrobiologia, 2021)